Venetoclax-Associated Cardiotoxicity in Acute Myeloid Leukemia: A Review of Mechanisms, Clinical Evidence, and Therapeutic Implications - VALENTINA RUSSO; ERIKA ESPOSITO; FRANCESCA SAULLO (International Journal of Pharmacy and Pharmaceutical Sciences, 2026)
The review aims to understand of the mechanisms involved in venetoclax-associated cardiotoxicity. A narrative literature search was conducted across PubMed, MEDLINE, and Embase for preclinical and clinical studies on venetoclax and cardiovascular events. Selected studies focused on cardiotoxic pathways, with data extraction targeting key pathophysiological drivers: oxidative stress, inflammation, and cellular apoptosis. A single retrospective analysis indicates that approximately 20% of patients receiving venetoclax in combination with a hypomethylating agent (HMA) experience cardiac events, frequently necessitating therapy suspension. Clinical studies have identified an imbalance between the production of reactive oxygen species (ROS) and the antioxidant defence system, as well as elevated levels of inflammatory markers, which contribute to the activation of apoptosis in cardiac cells. Venetoclax-associated cardiotoxicity has been linked to oxidative stress, inflammation, and apoptosis. Understanding these mechanisms is essential to develop targeted oncologic therapies that optimize treatment efficacy while ensuring cardiovascular safety.